COMMUNICATION ETHICS AS VIRTUAL VIRTUE CONTROL IN MEDIA BEHAVIOR SOCIETY IN THE DIGITAL AGE - Apdillah, Dicky; Harmika, Zuwairiah; Sahera, Miri; Harahap, Himmatul Ummi (Transpublika Publisher, 2022)
This paper delves at communication ethics as a means of controlling virtual piety in public media conduct in the digital age. The objective of this research is to describe, explain, and determine the role of communication ethics in the digital era as a control of virtual piety in public media behavior. The communication ethics notion employed is based on Haryatmoko's viewpoint and is supported by Habermas' theory of communication activities. This study employs qualitative research methods and a descriptive methodology. Observation and documentation were utilized as data collecting methods. The successfully gathered data is then examined, compared, and merged to generate a systematic, coherent, and comprehensive study result. According to the findings of this study, communication ethics is a set of standards, values, or a measure of good behavior in communication activities. In this regard, communication ethics as virtual piety control in public media behavior in this digital era is meant to ensure the attainment of general characteristics of acceptable norms in people's lives. Furthermore, it ensures individual autonomy through emancipatory powers, which leads to the establishment of a common will through logical dialogue. As a conclusion, communication ethics is an attempt to govern the communication process in order to ensure social stability in a pluralistic society in the digital era.